Judging the Nation: Early Nineteenth-Century British Evangelicals and Divine Retribution - Wolffe, John (Studies in church history, 2004)
Long had the ‘still small voice’ been spoke in vain,But God now thunders in an awful strain!Commercial woes brought down our nation’s pride,Our harvest fail’d, and yet we God defy’d:But now the ‘voice’ cries loud to all the Land,The ‘Rod’ is felt, Oh! may we see the Hand.’Tis God who speaks - ’Tis He who ’points the blow,’Tis God who’s laid the pride of Britain low!In these lines, written in November 1817, a lady member of a Newcastle-upon-Tyne Nonconformist congregation unambiguously attributed the death of Princess Charlotte to specific divine intervention. This conviction reflected that of her minister, James Pringle, in a recent sermon preached on an Old Testament text widely expounded at that time, the chastening rod (or voice) of God in Micah 6: 9. Such a perception of adverse national events as divine retribution for sin, comparable to prophetic interpretations of the history of Old Testament Israel, was a noticeable strand in early nineteenth-century British evangelical discourse.